2021
DOI: 10.1002/jcop.22712
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress among teachers of learners with special needs

Abstract: This study assessed the prediction of occupational stress through personality traits, gender and occupational stress among teachers of learners with special needs (TLSN) from the southwest, Nigeria. The transactional stress theory provided a framework for the study. Data were collected through a paper–pencil self‐completed questionnaire. Data collected were analysed by descriptive and inferential statistics at 95% confidence intervals (CIs) and p < 0.05. The response rate was 94.4%. A total of 287 male and 185… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(69 reference statements)
1
4
0
Order By: Relevance
“…34 Perceived behavioral control was assessed using four items with five responses, then rated into two categories: confident or not confident. 10 , 26…”
Section: Methodssupporting
confidence: 93%
See 3 more Smart Citations
“…34 Perceived behavioral control was assessed using four items with five responses, then rated into two categories: confident or not confident. 10 , 26…”
Section: Methodssupporting
confidence: 93%
“…The proportion of women who intended to stay at an MWH in the current study was lower than the 98% reported in Zambia. 25 This was also lower than results in studies in other African countries: 90% in Ghana, 10 66.6% in Zimbabwe, 42 and 94% in Zambia. 12 In spite of the perception that using MWHs is costly, about two-thirds (66.1%) of Kenyan women were very willing to stay at one.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Once you have a clear understanding of the problem, you can explore various alternatives for protection, prevention, and intervention (1). Occupational stress is one of the most common work-related health problems worldwide (1)(2)(3)(4)(5)(6)(7). Occupational stress is a well-documented issue that poses risks to both physical and mental health.…”
Section: Introductionmentioning
confidence: 99%